Тозаңды бөлшек поляризациясының әсерінен иондардың тозаңды бөлшекте классикалық шашырауы - Bastykova, N.Kh.; Kodanova, S.K.; Ramazanov, T.S.; Moldabekov, Zh.A. (Хабаршы. Физика сериясы, 2020)
In this paper, the influence of the magnetic field on the charging processes of dust particles in the gas discharge plasma were investigated. Calculations to study the charging processes of dust particle in the presence of the magnetic field were carried out numerically on the basis of particle-in-cell and Monte Carlo methods for the characteristic parameters of the gas discharge plasma. Estimates of the charge, the characteristic charging time of the dust particle, and the radial distribution of the density of electrons and ions at different values of the magnetic field were obtained. Taking into account the magnetic field led to a decrease in the absolute value of the charge of the dust particle, and an increase in the charging time of the dust particle. In the presence of the magnetic field in the vicinity of the dust particle, the density of electrons and ions decreases, which indicates a decrease in the dust particle charge, due to the restriction of the trajectory of plasma particles along the magnetic field lines.